Sustainable Energy Storage: Recent Trends and Developments toward Fully Organic Batteries. Issue 18 (22nd August 2019) - Friebe, Christian; Lex‐Balducci, Alexandra; Schubert, Ulrich S.
Abstract: In times of spreading mobile devices, organic batteries represent a promising approach to replace the well‐established lithium‐ion technology to fulfill the growing demand for small, flexible, safe, as well as sustainable energy storage solutions. In the last years, large efforts have been made regarding the investigation and development of batteries that use organic active materials since they feature superior properties compared to metal‐based, in particular lithium‐based, energy‐storage systems in terms of flexibility and safety as well as with regard to resource availability and disposal. This Review compiles an overview over the most recent studies on the topic. It focuses on the different types of applied active materials, covering both known systems that are optimized and novel structures that aim at being established. Abstract : The search for the green battery is at the center of numerous efforts during the last years. In particular, the replacement of environmentally questionable metals by more sustainable organic materials is on the current research agenda. This review presents recent results regarding the developments of organic active materials for electrochemical energy storage.